Civil Courage: Its Role in the Contemporary World and Its Place in Social Science - Misztal, Barbara A. (Stan Rzeczy, 2015)
The aim of this paper is to argue a need to re-evaluate the notion and function of civil courage in creating conditions for cohesive, just and pluralistic dimensions of contemporary societies. It will assert that courage can perform a vital social function by providing the basis for civic initiatives that affirm human rights and dignities, enrich the functioning of institutions and quality of civil society and enhance social or cultural change. Since the concept of courage is still commonly discussed using terms derived from the Classical Greece, I will delineate this ancient legacy and its contribution to the persistence of various obstacles and impediments in theorizing about courage. This will be followed by a discussion of the relevance of classical sociology’s input into today’s understanding of this notion, after which I will demonstrate that currently, as a result of border socio-political and technological transformations, this notion is in urgent need of re-evaluation. Finally, I will discuss the functions of civil courage in the contemporary world and its place in social science.